Ecological and Biomedical Significance of Soil and Aquatic Microbes in River Deltas - Ghosh, Rajrupa; Acharya, Rituparna (Research Perspectives of Microbiology and Biotechnology Vol. 5, 2024)
The world's deltas are home to a vast array of distinct soil and aquatic microbes, most of which take the form of bacteria, fungi, parasites, archaeans, actinomycetes, viruses, etc. They support the ecosystem in many ways, helping to preserve the equilibrium of the natural elements, the biogeological components, and the ecological components. In addition to offering plants environmental and natural defense against pests and diseases, soil microbes also help plants thrive. They play a critical role in converting nutrients and nitrogen into forms that plants can eat. The various functions that aquatic and soil bacteria play are decomposition, oxygen production, evolution, and symbiosis. Certain River Deltas have the highest concentrations of the saline soil-dependent bacterial and fungal community, whereas other River Deltas are enhanced with certain microbes that aid in soil remediation. In certain instances, variations in the C, N, and P ratios are caused by specific kinds of bacteria that break down hydrocarbons. Given that bacteria also produce various allergens and antigens, which are the primary causes of a variety of infectious diseases, some bacteria are used in research studies to produce anti-allergens and medicinal drugs.